Using MATLAB to Control Commercial Computational Electromagnetics Software - Haupt, R. L. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper provides details on how to use MATLAB to control some commercial electromagnetics software packages. FEKO is an example that can be directly called from MATLAB. Other commercial software, such as CST Microwave Studio and Ansoft HFSS, require a scripting language interface. An example of a design of an inset rectangular patch antenna is presented using a direct call to FEKO and a Visual Basic for Applications interface to CST Microwave Studio are presented.